R. K. Narayan as A Post-Colonial Novelist: Exploring R. K. Narayan's Ambivalent Attitude towards English Language in the Post-Colonial Era (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Narayan was born and grown up in a period when English education was already institutionalised in the Indian sub-continent. He received English education and used to write in English from the beginning of his literary career up to the end. However, he is seen to have used the English language and literary form to scrutinize colonialism and depict the Indian society continually under change due to the colonial rule. A part of this endeavour seems to be evident in his attitude towards the English language. His position in this regard is deemed quite ambivalent and complex óhe is aware that English is the language of the colonist, yet he is found to have accepted it for practical reasons. That is, his attitude towards the English language appears to have resulted from and shaped by the reality prevailing in the post-colonial setting. Narayanís life spanned the twentieth century, which meant that he belonged both to an old and a new India. The British presence in India had brought with it a large civil service, an educational system, and railways ñ all of these institutions the people of the subcontinent brought with enthusiasm. The British took English to India and the Indians retained a literary tradition which continues to delight and enrich us. The writer in the colonised country tended to soak up the culture of the colonial power and feel a familiarity and some affection for it, even though the experience of colonialism may have demoralized and destabilized his own colonised culture.